(untitled) (UNIZIK Journal of Marketing, 2025)
This study investigates the interplay between brand image, perceived product quality, and customer loyalty in Lagos, Nigeria’s Home Meal Replacement (HMR) market. Grounded in Expectation-Confirmation Theory, the research examines how brand promises (brand image) align with actual product experiences, specifically taste and convenience, to influence loyalty. Utilizing a Structural Equation Modeling on data from 412 urban consumers, the findings reveal that while brand image positively affects customer loyalty, its impact is considerably weaker than perceived product quality. Notably, perceived quality, particularly regarding taste and convenience, emerges as the strongest predictor of loyalty and fully mediates the relationship between brand image and loyalty. These results underscore the dominance of tangible product performance over abstract brand reputation in emerging markets like Nigeria, where consumers prioritize authentic taste and convenience. The study contributes to marketing theory by contextualizing Expectation-Confirmation Theory within a developing economy. It offers practical recommendations for HMR brand managers to focus on product excellence and innovation to foster customer loyalty.